Association between Insulin Resistance, Metabolic Syndrome and Nonalcoholic Fatty Liver Disease in Chinese Adults - Yan Jiang; Yafang Qian; Zhenya Song; Zhenyan Jiang; Xin Ying; Changjun Zhao (Tehran University of Medical Sciences, 2012)
"nBackground: The aim of this study was to assess the association between insulin resistance, metabolic syndrome and nonalcoholic fatty liver disease (NAFLD) in Chinese adults."nMethods: Fifty five subjects with NAFLD and 55 controls were enrolled for the study. Waist circumference, blood pressure, plasma triglyceride, high density lipoprotein cholesterol and fasting plasma glucose concentrations and homeostasis model assessment of insulin resistance (HOMA-IR) values as an index used to quantify insulin resistance were measured and analyzed. Logistic regression was analyzed to predict independent risk factors of NAFLD."nResults: The prevalence of metabolic syndrome in NAFLD group was obviously higher than in controls group (47.3% VS 3.6%, P<0.001). There were all significant differences of each component of metabolic syndrome and HOMA-IR values in comparison of nonalcoholic fatty liver disease (NAFLD) and controls group. In a logistic regression analysis, age, diastolic blood pressure, waist circumference and HOMA-IR were the covariates independently associated with the presence of NAFLD (Odds Ratio=1.107, 1.083, 1.218 and 16.836; 95% CI: 1.011～1.211, 1.001~1.173, 1.083～1.370 and 3.626~78.168, respectively; P<0.05)"nConclusion: NAFLD was closely associated with metabolic syndrome and insulin resistance was a very strong predictor of NAFLD.